Toughening in nanosilica-reinforced epoxy with tunable filler-matrix interface properties. (20th October 2019) - Picu, Catalin R.; Krawczyk, Krzysztof K.; Wang, Zehai; Pishvazadeh-Moghaddam, Hojabr; Sieberer, Manfred; Lassnig, Alice; Kern, Wolfgang; Hadar, Anton; Constantinescu, Dan M.
Abstract: In this work we develop an epoxy nanocomposite reinforced with silica nanoparticles in which the filler-matrix interfaces are functionalized with photosensitive phenylazide moieties, which allows controlling the interface mechanical properties by exposure to UV radiation. We demonstrate that the ability of the material to deform plastically and its toughness depend significantly on the strength of interfaces. Significant toughness improvement is obtained at low filling fractions (1 wt%) when using Stöber silica of 520 nm diameter with weak interfaces. We perform testing under different loading modes in order to control the crack tip plastic zone size, and observe substantial toughness improvement when crack tip plastic dissipation is enabled, which we associate with void growth at filler particles. Increasing the filler-matrix interfacial strength by photochemical (UV) activation of phenylazides leads to the reduction of the toughening effect.